Mitigasi Konflik di Lingkar Tambang: Studi Tentang Kontribusi Program Tanggung Jawab Sosial (CSR) PT. Vale Indonesia di Sorowako - Muhammad, Sawedi; Muhammad, Rahmat (Jurnal Keamanan Nasional, 2018)
Corporate Social Responsibility (CSR) has played strategic roles in mining industries in Indonesia over the last two decades. CSR contributes not only to improve basic physical infrastructures of local communities such as roads, bridges, health-center, schools and libraries but also to accommodate the needs of indigenous people in preserving and promoting their local art and culture. Some companies have been advancing their CSR roles to actively participate in mitigating the potential of trans-community conflict in their operation areas—a daunting task but worth executing—to ensure a sustained both social and government license to operate. The paper is aimed at unraveling CSR contribution of PT Vale Indonesia in transforming multicultural communities in its operation and what roles the company played in mitigating social conflict on the ground. The study finds out that company CSR management, which has adopted transparent, accountable and participatory methodologies have effectively improved the quality of life of local communities. The study also reveals that applying participatory methodologies in CSR management is not only enhance community participation in project-based, but also increase their awareness in mitigating social conflict in multicultural communities.